Application of Monte-Carlo Code to dose distribution calculation in a case of lung cancer by the emitted photon beams from Linear Accelerator - Le , Thanh Xuan; Nguyen Thi , Cam Thu; Tran , Van Nghia; Truong Thi , Hong Loan; Vo , Thanh Nhon (Nuclear Science and Technology, 2015)
The dose distribution calculation is one of the major steps in radiotherapy. In this paper the Monte Carlo code MCNP5 has been applied for simulation 15MV photon beams emitted from linear accelerator in a case of lung cancer of the General Hospital of Kien Giang. The settings for beam directions, field sizes and isocenter position used in MCNP5 must be the same as those in treatment plan at the hospital to ensure the results from MCNP5 are accurate. We also built a program CODIM by using MATLAB® programming software. This program was used to construct patient model from lung CT images obtained from cancer treatment cases at the General Hospital of Kien Giang and then MCNP5 code was used to simulate the delivered dose in the patient. The results from MCNP5 show that there is a difference of 5% in comparison with Prowess Panther program – a semi-empirical simulation program which is being used for treatment planning in the General Hospital of Kien Giang. The success of the work will help the planners to verify the patient dose distribution calculated from the treatment planning program being used at the hospital.